INCIDENCE OF ANEMIA IN PATIENT WITH NASOPHARYNGEAL CARCINOMA AT ENT-HNS DEPARTMENT WEST NUSA TENGGARA - Ni Ketut Susilawati; Hamsu Kadriyan (TALENTA PUBLISHER, 2019)
Introduction Nasopharyngeal carcinoma is common in China and Southeast Asia, includingIndonesia. The cases are often diagnosed in an advanced stage with a poor prognosis. Objective The purpose of this study was to determine the incidence of anemia in nasopharyngeal carcinoma patients in the ENT-HNS Department West Nusa Tenggara Hospital. Methods The methods of this research are a descriptive study that used data from the medical record of West Nusa Tenggara Hospital. The data were obtained between April 2017 to September 2017. Result During the study periods, we obtained 32 cases. 75% of patients were male and 25% female, with ratio 3: 1. According to the age, patients were distributed from 28 to 69 years old with peak incidence at 41-60 years old. Most patients were stage IV (68.75%). There was 87.51% patient with anemia in this research. However,the highest number was found mild anemia 59.38% and the most types of anemia were hypochromic microcytic. Conclusion The incidence of anemia in a patient with nasopharyngeal cancer in West Nusa Tenggara Hospital is 87.51%. Most of them were mild grade and hypochromic microcytic type